The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1051/0004-6361:20052741
|View full text |Cite
|
Sign up to set email alerts
|

Proper motion determination of open clusters based on the UCAC2 catalogue

Abstract: We present the kinematics of hundreds of open clusters, based on the UCAC2 Catalogue positions and proper motions. Membership probabilities were obtained for the stars in the cluster fields by applying a statistical method uses stellar proper motions. All open clusters with known distance were investigated, and for 75 clusters this is the first determination of the mean proper motion. The results, including the DSS images of the cluster's fields with the kinematic members marked, are incorporated in the Open C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1
5

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 18 publications
8
102
1
5
Order By: Relevance
“…Especially for the paper of Dias et al (2006) and DAML02 catalog, we showed that both sets agree with the present results, making us confident that the mean proper motions that are derived for the first time are correct.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Especially for the paper of Dias et al (2006) and DAML02 catalog, we showed that both sets agree with the present results, making us confident that the mean proper motions that are derived for the first time are correct.…”
Section: Discussionsupporting
confidence: 87%
“…The present version of the catalog contains 2174 objects, of which 1620 (74.5%) have published distances and ages, 1190 (54.7%) have published proper motions (most of them determined by our group (Dias et al (2001), Dias et al (2002b) and Dias et al (2006), hereafter DL06), and 543 (25.0%) have radial velocities.…”
Section: The Catalog Of Open Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several compilations of open stellar clusters are available in the literature, for example Lynga (1987), Loktin (1994), Mermilliod (1995, LL03, Kharchenko et al (2005), Piskunov et al (2007), WEBDA 1 and DAML 2 (Dias et al 2002(Dias et al , 2006. In Sect.…”
Section: Description Of the Samplementioning
confidence: 99%
“…The Sanders' algorithm, or some variation or refinement of it, has been and is still being widely used to estimate cluster memberships either as the only method or as part of a more complete treatment that includes, for example, spatial and/or photometric criteria. Some representative references are Wu et al (2002), Jilinski et al (2003), Balaguer-Núñez et al (2004), Dias et al (2006), Kraus & Hillenbrand (2007), and Wiramihardja et al (2009).…”
Section: Introductionmentioning
confidence: 99%